Love-Based Curriculum in Indonesian Madrasahs: A Conceptual Analysis Toward Inclusive-Humanistic Islamic Education - Mukhsin Mukhsin; Sahudi Sahudi; Yayat Hidayatulloh; Muhammad Nasir; Ilzam Hubby Dzikrillah Alfani (SYAMIL: Journal of Islamic Education, 2025)
Islamic education in Indonesia faces significant challenges in fostering genuine inclusivity and countering rising intolerance within increasingly pluralistic and globalized societies. In response, the Indonesian Ministry of Religious Affairs has proposed the innovative Love-Based Curriculum (LBC) for madrasahs. This study aims to critically analyze the LBC’s conceptual framework as a model for inclusive-humanistic Islamic education and evaluate its proposed implementation strategies. Employing a qualitative library research design, this study systematically analyzed the primary policy document, Panduan Kurikulum Berbasis Cinta di Madrasah (2025), alongside relevant academic literature on inclusive pedagogy and Islamic curriculum theory. Data were examined through thematic analysis. The findings indicate that the LBC conceptualizes inclusivity through a three-pronged approach: theological deconstruction emphasizing divine attributes of love (Al-Wadud, Ar-Rahman), pedagogical integration via a hybrid ARKA model, and preventive social mechanisms rooted in restorative justice. However, the analysis also reveals conceptual tensions, such as the potential paradox between standardizing 'love' in a curriculum and its inherently subjective nature, alongside practical challenges related to teacher readiness and socio-cultural barriers. This study concludes that while the LBC presents a groundbreaking normative framework, its transformative potential hinges on addressing these contradictions through contextual adaptation, robust teacher training, and further empirical research. The study contributes a critical conceptual evaluation essential for stakeholders implementing value-based educational reforms in Islamic schooling contexts.